Greek medical papyri: text, context, hypertext - Reggiani, Nicola (Archiv für Papyrusforschung und verwandte Gebiete / Beiheft, 2019)
Frontmatter -- Table of contents -- Introduction / Reggiani, Nicola -- I. MEDICAL TEXTS -- From Prescription to Practice: The Evidence of Two Medical Papyri from Roman Egypt / Andorlini, Isabella -- Medizinische Texte im Wandel der Zeiten. Schriftträger und Buchtypen im nachchristlichen Ägypten / Jördens, Andrea -- Riconsiderazioni sull'Anonimo Londinese: progressi e punti ancora irrisolti / Manetti, Daniela -- Qui est donc l'auteur de l'Anonyme de Londres ? Sa personnalité et son émergence à la polémique / Jouanna, Jacques -- Des cailles et de la ciguë. A propos de l'Anonyme de Londres (P.Lond.Lit. 165, Brit.Libr. inv. 137) col. XXVI, 16-19 / Boudon-Millot, Véronique -- Un corpo che prende forma (addendum): papiri ippocratici e dintorni / Roselli, Amneris -- Il lessico delle cure e della farmacologia in papiri medici da Ossirinco / Fausti, Daniela -- Römische militärmedizinische Versorgung und Berichterstattung der Soldaten: Ein Vorschlag zur Kategorisierung der Urkunden / Bernini, Andrea / Kaiser, Anna Maria -- II. THE DOCTORS' CONTEXT -- The Greek Doctor in Ptolemaic, Roman, and Byzantine Egypt / Hanson, Ann E. -- Punishing the Incompetent Physician: Some Neglected Cases / Nutton, Vivian -- Medici Docti in Verse Inscriptions / Lougovaya, Julia -- Περίψημα. A Question of Life and Death in a Private Letter from the Eastern Desert of Egypt / Bülow-Jacobsen, Adam / Cuvigny, Hélène -- Genetic Criticism and the Papyri: Some Suggestions / Cribiore, Raffaella -- La scienza medica nei papiri ercolanesi / Mastro, Gianluca Del -- Latin Books in Late Antique Egypt: Some Tentative Remarks / Corso, Lucio Del -- Terminologia tachigrafica in alcune similitudini del De virginitate di Basilio d'Ancira / Menci, Giovanna -- III. THE DIGMEDTEXT PROJECT -- Linguistic and Philological Variants in the Papyri: A Reconsideration in Light of the Digitization of the Greek Medical Papyri / Reggiani, Nicola -- Medicalia Online: tecnicismi medici tra passato e presente / Bonati, Isabella -- L'uso del καυτήρ nei papiri medici e nelle testimonianze letterarie / Bertonazzi, Francesca -- La digitalizzazione dei papiri medici di Antinoupolis: caratteristiche e particolarità / Corazza, Francesca -- Bio-bibliografia ragionata di Isabella Andorlini / Iori, Luca / Centenari, Margherita -- Indices